Beyond an inflammatory mediator: Interleukin‐1 in neurophysiology - Tatiane S. Lima (Experimental Physiology, 2023)
Abstract Since its discovery in the early 1940s, the interleukin‐1 (IL‐1) cytokine family has been associated primarily with acute and chronic inflammation. The family member IL‐1β is produced by different leucocytes, endothelial cells and epithelial cells. This cytokine has been characterized as a key modulator of inflammation and innate immunity because it induces the transcription of several downstream inflammatory genes. More recently, several groups have demonstrated that IL‐1β production is also required to maintain homeostasis in several organ systems. This review focuses on providing an overview of the more recently characterized role of IL‐1β in the physiology of the CNS. So far, IL‐1β signalling has been implicated in neuronal survival, neurite growth, synaptic pruning, synaptic transmission, neuroplasticity and neuroendocrine functions.